BIM 소프트웨어 호환성 분석 : 사용자정의 속성정보인 GBS를 중심으로 - 강승희; 하지원; 주태환; 정영수; Kang, Seunghee; Ha, Jiwon; Ju, Taehwan; Jung, Youngsoo (한국건설관리학회 논문집, 17(2), 2016)
The utilization of Building Information Modeling (BIM) has increased in order to enhance the integration of information for management and resources throughout the construction projects. Therefore, various BIM softwares have been used under open BIM environments in the building and plant construction industry. However, it has obstructive factors due to the lack of interoperability. In order to address this problem, this study conducted an interoperability analysis of BIM software focused on user-defined properties for enhanced function and efficiency. Result of the analysis shows that authoring tools have more interoperability problems than viewer tools and simulation tools have. In terms of interoperability, user-defined properties outperforms than those of system basic properties and logic data. Therefore, it was found that functional improvement and workload minimization in BIM can be attained by applying the GBS (an user-defined property for automatic manipulation of BIM proposed by Jung et al. 2013) that enables automatic link between geometric data and non-geometric data. In this respect, this study concludes that the application of user-defined property (e.g. GBS) can be an effective method for information integration throughout construction projects. 건설 프로젝트에서 발생하는 다양한 정보를 통합관리하기 위한 BIM의 실무활용이 확산되고 있으며, 활용 형태 또한 점차 고도화되고 있다. 이에 건축 및 플랜트산업에서 BIM 환경구축을 위해 다양한 BIM 소프트웨어들이 사용되고 있으나, 정보 호환성 및 통합성 부족은 주요 장애요인으로 지적되고 있다. 이러한 배경에서, 본 연구에서는 사용자정의 속성정보 (GBS)를 기반으로 한 BIM 활용의 기능적 고도화 및 업무효율화 방안을 검증하기 위해 BIM 소프트웨어간 호환성 테스트를 실시하였다. 호환성 테스트 결과, 'BIM 시스템 관점'에서는 Viewer Tool과 Simulation Tool이 Authoring Tool에 비해 정보 호환성이 전반적으로 높았으며, 'BIM 정보 관점'에서는 사용자정의 속성정보 (GBS)의 호환성이 시스템 기본 속성정보 및 Logic 정보보다 높았다. 즉, 도형정보와 비도형정보의 연계 자동화를 가능케하는 GBS의 적용을 통해 BIM 활용의 기능적인 고도화 및 업무부담 최소화가 가능하며, 또한, 추후 사용자정의 속성정보를 활용한 도형과 다양한 비도형정보와의 정보연계에 대한 연구가 이뤄진다면, 건설 프로젝트의 통합관리에 한층 가까워질 것이라 기대된다.